Strong Summability of Faber Series and Estimates for the Rate of Convergence of a Group of Deviations in a Closed Domain with Piecewise-Smooth Boundary - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We establish estimates for groups of deviations of Faber series in closed domains with piecewise-smooth boundary.